Paraplegia and squamous cell carcinoma of the bladder in young women: findings from a case-control study. - Dolin, P; Darby, S; Beral, V (1994)
A death certificate-based case-control study was conducted on 207 women aged 25-44 who died of bladder cancer in England and Wales in the period 1971-89 and 411 controls matched on sex, year of death and age at death. An odds ratio of 12.0 (95% CI 1.5-99.7) was found for women with a history of paraplegia. Four of the six paraplegic women were reported to have had squamous cell carcinoma of the bladder compared with only 19 of the 201 non-paraplegic women. These findings suggest that squamous cell carcinomas of the bladder, especially in paraplegics, may be the result of chronic urinary tract infection.